Optimalisasi Pelaksanaan Pengembangan Profesional Berkelanjutan bagi Perawat - Purwanti, Enny Sri; Hariyati, Rr.Tutik Sri; Asmara, Amelia; Wildani, Andi Amalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze the implementation of continuous professional development in hospitals. The method used is a case report including assessment, problem identification, problem analysis using fishbone, preparation of a Plan of Action (PoA), implementation, and evaluation. The research results show that the main problem is that continuous professional development could have been more optimal. The problem was solved using Kurt Lewin's planned change approach, with the implementation preparing a draft guide for implementing sustainable professional development. Conclusion: The situation in hospital management is that the performance of continuous professional development could be more optimal. The strategy to optimize the implementation of ongoing professional development is to create a guide that becomes a reference for nurses following the continuous professional development program. Keywords: Nursing Manager, Guide, Continuous Professional Development, Planned Change